Alkali activated lightweight mortars for passive fire protection: A preliminary study. (20th January 2019) - Carabba, Lorenza; Moricone, Raffaela; Scarponi, Giordano Emrys; Tugnoli, Alessandro; Bignozzi, Maria Chiara
Graphical abstract: Highlights: Fly ash was successfully alkali activated at room temperature. The use of expanded perlite and H2 O2 allowed obtaining lightweight mortars. Numerical simulations predicted a satisfactory fire behaviour. Alkali activated lightweight mortars were able to outperform cement-based ones. Abstract: Alkali activated lightweight mortars, obtained by room temperature activation of coal fly ash, were studied as passive fire protection systems for steel elements. Physical, mechanical and thermal properties were investigated as a function of the compositional Si/Al molar ratio and of the amount of lightweight aggregate and foaming agent. Experimental findings were used as input data to assess their fire resistance by finite volume simulations. Results pointed out that the optimized alkali activated lightweight mortars are able to outperform alternative commercial cement-based mortars, thus representing a promising technology.